2018
DOI: 10.3892/ol.2018.8415
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hepatic metastases with computed tomography‑guided interstitial brachytherapy

Abstract: The aim of the present study was to evaluate the efficacy, safety and tolerability of local treatment of liver metastases of various types of cancer using brachytherapy with computed tomography (CT) imaging. Retrospective analysis of 61 patients with unresectable hepatic metastases treated with CT-guided interstitial high dose rate (HDR) brachytherapy of the liver between April 2014 and December 2016 was performed. Patients were treated with a single fractional dose of 15-25 Gy. Statistical analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…The study by Kieszko et al evaluated the clinical outcome of 61 patients with 73 liver secondary tumors treated with HDR-BT. LC and OS rates were 88.7%, 70.7% and 96.7%, 79.6% at 6 and 12 months respectively (45). Omari et al investigated the results of 14 patients with 54 renal cell liver metastases, treated with liver BT, reporting LC rate of 92.6% at 10.1 months and median OS of 51.2 months (62).…”
Section: Clinical Resultsmentioning
confidence: 99%
“…The study by Kieszko et al evaluated the clinical outcome of 61 patients with 73 liver secondary tumors treated with HDR-BT. LC and OS rates were 88.7%, 70.7% and 96.7%, 79.6% at 6 and 12 months respectively (45). Omari et al investigated the results of 14 patients with 54 renal cell liver metastases, treated with liver BT, reporting LC rate of 92.6% at 10.1 months and median OS of 51.2 months (62).…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Kieszko et al reported on 61 patients undergoing iBT for unresectable hepatic metastases of mixed histologies [ 31 ]. They reported OS rates after 6 months and 12 months of 96.7 and 79.6%, while the PFS rates were 78.1 and 53.8%, and the LRFS rates were 88.7 and 70.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of toxicity, almost 20% of patients showed higher levels of gastrointestinal toxicity or liver enzymes. Additionally, mature monoinstitutional experiences with IRT demonstrated the advantage of focal high-dose-rate interstitial radiotherapy in effectivity and economics ( 31 35 ).…”
Section: Evidencementioning
confidence: 99%